Evaluation and Comparison of Anti-Epileptic Activity of Methanolic Extracts of Seeds of Cuminum Cyminum L. and Centratherum Anthelminticum L. in Seizure Model - Raana Mahmood; Rahila Najam; Mohammad Irfan Khan; Talat Tariq (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: Evaluation and comparison of anti-epileptic activity of methanolic extracts of seeds of Cuminum cyminum L. and Centratherum anthelminticum L. in strychnine-induced seizure model. Methods: The study was conducted in the Department  of  Pharmacology,  University  of  Karachi.  After  15  days of dosing, experiment was performed. A total of 40 healthy mice were selected from animal house of  the Pharmacology department, University of Karachi, and were equally divided into four groups. Group 01 was on DMSO (dimethyl sulphoxide) organic solvent as control; Group 02 was on methanolic extract of  Cuminum cyminum L. (500 mg/kg); Group 03 was on methanolic extract of Centratherum anthelminticum L. (200 mg/kg) and Group 04 was on reference drug diazepam (3 mg/kg). On the day of experiment, after giving doses of DMSO, methanolic extract of Cuminum cyminum L., methanolic extract of Centratherum anthelminticum L. and diazepam,  respectively  to  all  groups,  strychnine  was  administered  and  animals  were observed for latency period and duration of Mortality rate was also evaluated. Results: Group 02 and 03, receiving methanolic extracts of Cuminum cyminum L. and Centratherum anthelminticum L. showed significant seizure protection as observed by delayed seizure onset (p <0.001) and decreased total duration of convulsions in groups 02 and 03 (p£ 0.01, p£ 0.05) respectively. The mortality rate also decreased significantly (p £ 0.05) in comparison with group 01. Conclusion: Anticonvulsant activity of methanolic extracts of Cuminum cyminum L. and Centratherum anthelminticum L. could be due to their antioxidant activity and further enhanced by potentiation of GABAergic and glycinergic activity. Further studies are required to confirm exact mechanism of action.